2011
DOI: 10.1073/pnas.1100156108
|View full text |Cite
|
Sign up to set email alerts
|

Critical roles of chemokine receptor CCR10 in regulating memory IgA responses in intestines

Abstract: Chemokine receptor CCR10 is expressed by all intestinal IgA-producing plasma cells and is suggested to play an important role in positioning these cells in the lamina propria for proper IgA production to maintain intestinal homeostasis and protect against infection. However, interfering with CCR10 or its ligand did not impair intestinal IgA production under homeostatic conditions or during infection, and the in vivo function of CCR10 in the intestinal IgA response remains unknown. We found that an enhanced gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 36 publications
3
70
0
Order By: Relevance
“…In addition, ILFs have been shown to increase in number in the small and large intestines of mice lacking CCR10, which show normal numbers of IgA-secreting cells in the intestine 17 . Enlarged ILFs are considered to serve to compensate for the defective recruitment of Ccr10 À / À IgAsecreting cells to the intestine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, ILFs have been shown to increase in number in the small and large intestines of mice lacking CCR10, which show normal numbers of IgA-secreting cells in the intestine 17 . Enlarged ILFs are considered to serve to compensate for the defective recruitment of Ccr10 À / À IgAsecreting cells to the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…CCR9 is responsible for the homing to the small intestine 16 , whereas CCR10 contributes to the migration to both the small and large intestines 17,34,35 . IgA þ cells in the caecal patch expressed higher levels of CCR9 and CCR10 than the cells in Peyer's patches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These small lymphoid structures seated all over the small bowel are highly dynamic serving as an important inductive site for IgA synthesis confronting changes in the microbiota (15,16). ILF hyperplasia and uncontrolled growth of commensals were shown in an activation-induced cytidine deaminase (AICDA) null mice, where class switch recombination and somatic hypermutation (SHM) are inhibited (17), whereas reduced number of ILFs were detected in antibiotic-treated or in germ-free mice (18,19). Little is known about human ILFs in general and to our knowledge, no studies of ILFs from the intestinal allograft have been reported.…”
Section: Introductionmentioning
confidence: 99%